Effect of different drying treatments on the concentration of nutrient content and functional properties of black turmeric (Curcuma caesia) - Datta, Sritama; Kumari, P Vasantha (Journal of Postharvest Technology, 2024)
Curcuma caesia is the blackish-blue variant of yellow turmeric. Plant rhizome is popularly used by tribal communities due to its medicinal properties, still it remains unknown and underutilized by majority of population. The study aims to analyse the effect of different drying treatments (sun drying, hot-air-oven drying, and microwave drying) on nutrient composition and phytochemical content of black turmeric. Results showed that the Hot-air-oven Dried sample had significantly (p<0.05) higher retention of protein, total phenolic and flavonoid content. The high phenolic and flavonoid content of the Hot-air-oven dried sample contributed to higher antioxidant capacity compared to other dried samples.